High noon the inside story of Scott McNealy and the rise of Sun Microsystems - Southwick, Karen (John Wiley, 1999)
"High Noon is the inside story of Sun's rise to power, from its shaky start in Silicon Valley through its transformation under the aggressive and inspirational leadership of McNealy. Karen Southwick reveals the behind-the-scenes maneuverings of McNealy and Sun, with candid interviews from the key players and insights into the inner workings of the high-tech industry." "This book examines how scrappy underdog Sun.